Novel Worm-like Micelles for Hydrochloride Doxorubicin Delivery: Preparation, Characterization, and In Vitro Evaluation - Yang, Ya-Ni; Ge, Chen; He, Jun; Lu, Wei-Gen (Pharmaceutical Fronts, 2022)
Doxorubicin hydrochloride (DOX) is one of the widely used antineoplastic agents in treating various cancers, yet it is always associated with the occurrence of adverse reactions that limit its clinical use. Currently, encapsulating DOX in micelles may represent a promising strategy to reduce toxicity and side effects of the drug. This study aimed to explore a novel acitretin-based surfactant (ACMeNa) with good solid stability to encapsulate DOX to form micelles (ACM-DOX). In this work, ACM-DOX micelles were prepared by a microfluidic method free of organic solvents. The characteristics of ACM-DOX micelles were assessed, including morphology, particle size, stability, entrapment efficiency, and drug loading. An in vitro cytotoxicity experiment of the micelles on MDA-MB-231 (a human breast cancer cell line) was also performed. The micelle formation mechanism suggested that the insoluble ACMeNa/DOX complex was formed by electrostatic interaction, and subsequently encapsulated by self-assembly into micelles. The designed ACM-DOX micelles had an average particle size of 19.4 ± 0.2 nm and a zeta potential of −43.7 ± 2.4 mV, with entrapment efficiency and drug loading efficiency of 92.4 ± 0.5% and 33.4 ± 0.3%, respectively. The ACM-DOX micelles had worm-like structures under a Cryo-transmission electron microscope and exhibited good stability within 8 hours after reconstitution and 4- to 32-fold dilution of its reconstituted solution. ACM-DOX micelles released 80% of DOX within 24 hours in a medium of pH = 5.0, and its drug profile can be described by a first-order model. Moreover, ACM-DOX micelles showed cytotoxicity against MDA-MB-231 in a dose-dependent manner, and displayed a higher antitumor activity as compared with free DOX, with IC50 values of DOX and ACM-DOX micelles being 6.80 ± 0.50 and 4.64 ± 0.32 μg/mL, respectively. Given above, ACMeNa has great application potential as a DOX carrier for the treatment of cancers.
Keywords: doxorubicin hydrochloride; ACMeNa surfactants; micelles; microfluidics